Coronavirus disease 2019 and gender-related mortality in European countries: A meta-analysis. (November 2020) - Pérez-López, Faustino R.; Tajada, Mauricio; Savirón-Cornudella, Ricardo; Sánchez-Prieto, Manuel; Chedraui, Peter; Terán, Enrique
Highlights: The article presents a meta-analysis of COVID-19-related mortality data from the Global Health 50/50 repository. COVID-19-related mortality is higher in European men than in European women. The male–female mortality risk ratio is 1.60 (95 % CI 1.53, 1.68). Abstract: Objective: To examine mortality rates related to coronavirus disease 2019 (COVID-19) by gender among European countries. Methods: PubMed, preprint medRxiv and bioRxiv repositories, and Google were searched for the terms COVID-19, mortality rates, gender, and Europe. Only Google provided a website with appropriate information. COVID-19 cases and deaths from European countries were extracted by gender from the Global Health 50/50 repository up to May 23, 2020. Extracted data included country, the total number of COVID-19 cases and the number of related deaths by gender. Random effects models with the inverse variance method were used for meta-analyses. Results are reported as death risk ratios (RRs). Results: We identified information from 23 European countries that reported separately by gender mortality rates related to COVID-19. The sample comprised 484, 919 men and 605, 229 women positive for COVID-19. The mortality rate was significantly higher in men than in women (risk ratio = 1.60, 95 % confidence interval [CI] 1.53, 1.68). The trend was similar when countries reporting < 5000, or < 10, 000 cases were excluded from the analysis (RR = 1.60, 95 % CI 1.52, 1.69 and RR = 1.68; CI 1.62, 1.76, respectively). Conclusion: In Europe, the new zoonotic coronavirus causes significantly more deaths in men than in women.